Diet Control and Swimming Exercise Ameliorate HFD-Induced Cognitive Impairment Related to the SIRT1-NF-κB/PGC-1α Pathways in ApoE-/- Mice - Wei Wei; Zhicheng Lin; PeiTao Xu; Xinru Lv; Libin Lin; Yongxu Li; Yangjie Zhou; Taotao Lu; Xiehua Xue (Neural Plasticity)
High-fat diet- (HFD-) induced neuroinflammation may ultimately lead to an increased risk of cognitive impairment. Here, we evaluate the effects of diet control and swimming or both on the prevention of cognitive impairment by enhancing SIRT1 activity. Twenty-week-old ApoE-/- mice were fed a HFD for 8 weeks and then were treated with diet control and/or swimming for 8 weeks. Cognitive function was assessed using the novel object recognition test (NORT) and Y-maze test. The expression of sirtuin-1 (SIRT1), peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), brain-derived neurotrophic factor (BDNF), nuclear factor kappa B p65 (NF-κB p65), interleukin-1β (IL-1β), and tumour necrosis factor-α (TNF-α) in the hippocampus was measured by western blotting. The levels of fractional anisotropy (FA), N-acetylaspartate (NAA)/creatine (Cr) ratio, choline (Cho)/Cr ratio, and myo-inositol (MI)/Cr ratio in the hippocampus were evaluated by diffusion tensor imaging (DTI) and magnetic resonance spectroscopy (MRS) using 7.0-T magnetic resonance imaging (MRI). Our results showed that cognitive dysfunction and hippocampal neuroinflammation appeared to be remarkably observed in apolipoprotein E (ApoE)-/- mice fed with HFD. Diet control plus swimming significantly reversed HFD-induced cognitive decline, reduced the time spent exploring the novel object, and ameliorated spontaneous alternation in the Y-maze test. Compared with the HFD group, ApoE-/- mice fed diet control and/or subjected to swimming had an increase in FA, NAA/Cr, and Cho/Cr; a drop in MI/Cr; elevated expression levels of SIRT1, PGC-1α, and BDNF; and inhibited production of proinflammatory cytokines, including NF-κB p65, IL-1β, and TNF-α. SIRT1, an NAD+-dependent class III histone enzyme, deacetylases and regulates the activity of PGC-1α and NF-κB. These data indicated that diet control and/or swimming ameliorate cognitive deficits through the inhibitory effect of neuroinflammation via SIRT1-mediated pathways, strongly suggesting that swimming and/or diet control could be potentially effective nonpharmacological treatments for cognitive impairment.